Organochlorine pesticide exposure among agricultural workers in Colombian regions with illegal crops: an exploration in a hidden and dangerous world (2010)
A previous study suggested that banned organochlorine pesticides were being used to protect illegal crops from pests. The study herein explored the exposure of individuals living in a region with such crops. Samples from 99 individuals were collected during 2005 and 2006 and organochlorine pesticides were quantified using chromatography in serum samples. We detected heptachlor (72.73%), 4,4-DDE (19.19%), aldrin (15.15%), ?-chlordane (12.12%), dieldrin (11.11%), ?-chlordane (10,10%), ?-endosulfan (8.08%), endosulfan (6.06%), ?-endosulfan (5.05%), oxychlordane (3.03%), 4,4-DDT (3.03%), and 2,4-DDT (2.02%). Heptachlor had a skewed and negative distribution (median: 8.69 ng/l and maximum: 43.8 ng/l). A two-dimensional biplot suggested that mixtures present were endosulfan/4,4-DDT, aldrin/?-chlordane, and oxychlordane/?-endosulfan/dieldrin. We did not identify variables associated with exposure levels. These data suggest that banned organochlorine pesticides are used. This is an example of research in a war context, where the problems related with pesticides are complex, and their implications go beyond a toxicological or epidemiological viewpoint.